ANALISIS FAKTOR PERSONAL HYGIENE DAN SANITASI LINGKUNGAN DENGAN DEMAM THYPOID DI WILAYAH KERJA PUSKESMAS KEMALARAJA KABUPATEN OKU - Yustati, Eva; Dinata, Arda Surya (Jurnal Kesehatan Abdurrahman, 2023)
Disease, in an area depends on the presence of humans who understand the environmental conditions suitable for the life of disease-causing microorganisms. environmental hygiene, sanitation and poor personal hygiene are factors that can increase the spread of diseases, especially typhoid. Factors related to the incidence of typhoid fever are related to clean and healthy living behavior, such as the quality of personal hygiene and environmental sanitation and the lack of public knowledge that does not support a healthy life. The research method uses a cross sectional design. Data are analyzed using the Chi-square test. The population of the entire Kemalaraja Village community is 389 people. The sample taken is simple random sampling. based on the formula contained in Iwan Ariawan's book (2011). amounting to 193 samples. The results of Univariate analysis of bad hand washing habits were 24.9% of respondents, 75.1% of respondents in the category of good hand washing. The unavailability of landfills was 43 (22.3%) of respondents, 77.7% of respondents had available landfills, 23.3% of respondents had bad knowledge, 76.7% of respondents had good knowledge. The results of the chi square test obtained a p value of 0.000 < (0.05) meaning that there is a significant relationship between hand washing habits and the incidence of typhoid fever, p value 0.000 < (0.05) meaning that there is a significant relationship between landfills and the incidence of fever. typhoid, p-value 0.001 < (0.05). This means that there is a significant relationship between knowledge and the incidence of typhoid. Conclusion: There is a significant relationship between hand washing habits, trash bins and knowledge with the incidence of typhoid fever